Synthesis and Characterization of CuO Nanoparticles and Acute Lethal Studies in Eudrilus eugeniae Earthworm - J, Mohamad Rafeek; M, Meeramaideen; P, Suganthi; P, Rajasekar; A, Jafar Ahamed (Asian Journal of Biological and Life Sciences)
Introduction: Metal oxide nanoparticles are widely used in numerous fields due to their wide interacting properties. Copperoxide nanoparticles (CuO NPs) has various application in industrial, agriculture, bioremediation and pharmaceutical. Aim: Our study is aimed to chemically synthesize the CuO NPs and revealed acute toxicity on earthworm Eudrilus eugeniae. Materials and Methods: CuO NPs are chemically synthesized by simple precipitation method. Nanoparticles characterization are studied by UV, FTIR, XRD, FESEM with EDAX. The acute toxicity of the CuO NPs on earthworm Eudrilus eugeniae are studied. Results: UV-Vis and FTIR spectroscopic studies revealed the gap energies and the functional group of the synthesized particles. XRD, FESEM with EDAX also evidenced the morphology of CuO NPs as spherical structure with 24nm size. The acute toxicity of the different concentrations CuO NPs are tested on acclimatized earthworm Eudrilus eugeniae (n=20) for 14 days. The lethal concentration (LC50) of the CuO NPs on adult earthworm E. eugeniaeis identified between 1100 to 1200ppm. Conclusion: The chemically synthesized CuO NPs confirmed particle size and nature. The emergence of CuO NPs into the soil medium becomes toxic to the earthworm
Keywords: Copperoxide nanoparticles; Earthworm; Eudrilus eugeniae.; FTIR; LC50; SEM